Effect of Corrugation Angle and Direction on the Performance of Corrugated Steel Plate Shear Walls - Hayder Fadhil; Amer Ibrahim; Mohammed Mahmood (Salehan Institute of Higher Education, 2018)
Corrugated steel plate shear wall (CSPSW) is one of the lateral resistance systems which consists mainly of steel frame (beam and column) with vertical or horizontal corrugated steel plate connected to the frame by weld, bolts or both. This type of steel shear wall characterized by low cost and short construction time with high strength, ductility, initial stiffness and excellent ability to dissipate energy. The aim of this paper is to evaluate the effect of corrugation angle and its direction on the performance of CSPSW under cyclic loading. The Finite element analysis was employed to achieve the research aim. The FE models were validated with experimental data available in the literature. Results reveal that the corrugation angle has a clear influence on initial stiffness, strength, ductility, and energy dissipation of CSPSW. The optimum performance of CSPSW can be obtained with angles of 30o for CSPSW with vertical corrugation and 20o for CSPSW with horizontal corrugation. The use of CSPSW with vertical corrugation provides higher strength, stiffness, and ductility compared to CSPSW with horizontal corrugation. Therefore, it is recommended to use CSPSW with vertical corrugation.